Breaking the chains of culture : building trust in individuals, teams, and organizations - Vukotich, George (Emerald Publishing Limited : Information Age Publishing, 2010)
Breaking the Chains of Culture looks at trust in organizations and the role it plays in building successful relationships at the individual, team, and organization level. Based on experience working with thousands of individuals in hundreds of organizations we have found there are basic common barriers that keep us from being as effective as possible. Our leaders have said one thing and acted on another for so long they are seen as powerless. Our cultures and actions have driven our people to become numb and selfcentered. Our reward systems are seen as a zero sum game where one individual can get more only at the expense of another.Breaking the Chains of Culture shows how organizations can turn these issues around. A number of case studies take the reader through examples leaving them with a framework to be more effective in their relationships with others. Readers work through exercises to help them better understand themselves and their organization. They develop a clearer understanding of their relationships with others and see how their interactions can impact their overall effectiveness. Learning about themselves and the others around them allows the reader to build long term relationships base on trust rather than just short term interactions based on surface level words and temporary needs. A must read for anyone who needs relationships to be effective.